Implementation of future agricultural engineers' training technology in the informational and educational environment - Aleksandr D. Uchitel; Ilona V. Batsurovska; Nataliia A. Dotsenko; Olena A. Gorbenko; Nataliia I. Kim (Academy of Cognitive and Natural Sciences, 2021)
The article presents the implementation of future agricultural engineers' training technology in the informational and educational environment. To train future agricultural engineers, it is advisable to form tutorials for the study of each discipline in the conditions of informational and educational environment. Such tutorials are an assistance in mastering both theoretical material and course navigation, where interactive electronic learning tools are presented to perform tasks in the informational and educational environment. Higher education applicants perform such tasks directly in the classroom with the help of gadgets or personal computers. The final grade is formed from the scores obtained in the classroom and the rating of higher education applicants while studying in the informational and educational environment. The outlined approach is able to help in the quality of learning content. The use of interactive audiovisual online tools allows to get acquainted with the theoretical, practical and experimental provisions clearly, it is important for the training of future agricultural engineers. At the end of the experiment, it can be argued that the developed technology increases the level of motivation and self-incentive to work in the informational and educational environment. The application of the presented technology provides an opportunity to combine the educational process in the classroom with learning in the informational and educational environment, forms analytical abilities and competencies in professional activity. The reliability of the obtained results was checked using the Kolmogorov-Smirnov criterion. It is determined that when using this technology in the educational process, the indicators in the experimental group increased, which displays the effectiveness of training bachelors in agricultural engineering in the conditions of informational and educational environment.